Directional versus orbital atherectomy of femoropopliteal artery lesions: Angiographic and intravascular ultrasound outcomes. Issue 4 (16th July 2022) - Babaev, Anvar; Halista, Michael; Bakirova, Zulfiya; Avtushka, Valeryia; Matsumura, Mitsuaki; Maehara, Akiko
Abstract: Objectives: The aim of this study was to compare the ability of two different atherectomy modalities, the directional atherectomy system (DAS) and the orbital atherectomy system (OAS), to modify plaque and augment luminal gain as evaluated by angiography and intravascular ultrasound (IVUS) in patients with symptomatic femoro‐popliteal peripheral arterial disease (PAD). Background: Atherectomy is frequently utilized in the treatment of complex PAD. To date, there are no head‐to‐head comparisons of existing devices and their selection is based mostly on operator preference rather than on supportive data. Methods: This was a single‐center, prospective, randomized trial designed to assess the impact of DAS in comparison to OAS on atherosclerotic plaque. Pre‐ and postatherectomy lesion characterization was performed by angiography and IVUS. Drug‐coated balloon (DCB) angioplasty was performed after atherectomy with similar analysis repeated. Results: Sixty patients were randomized to undergo either DAS or OAS. Pretreatment angiographic and IVUS characteristics were similar in the DAS and OAS groups. DAS led to a greater reduction in plaque volume throughout the entire lesion (5.9% vs. 1.1%, p  = 0.003). This corresponded to a greater increase in total vessel and lumen volume by IVUS (161.5 mm 3 vs. 50.2 mm 3, p  = 0.001; 178.6 mm 3 vs. 47.0 mm 3, p  = 0.004, respectively), as well as a reduction in angiographic stenosis (40% vs. 70%, p  < 0.001). After DCB, 10 patients required stenting for suboptimal results in the OAS group compared with two in the DAS group ( p  = 0.021). Conclusions: Compared to OAS, DAS demonstrated a greater plaque volume reduction and luminal gain with significantly fewer stents needed post‐DCB.